(untitled) (PANGEEA, 2025)
Toponimic of Sâncel District, Alba County. District of Sâncel has in its structure villages: Iclod, Pănade and Sâncel. From the historical documents about those villages we preserved more geographical names "border signs", or "tags places". Those three villages are considerably old, being documentary certificate (Iclod-1347, Pănade-1290, Sâncel-1252-1271). During the centuries they had many geographical names related with the owners of the lands or after their origins, descendents. The inhabitants of the area had in common traditions and customs which are very well preserved till our days.